2018
DOI: 10.1002/hep.30212
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Immune Response to Tumor‐Associated Antigens and Immune Cell Profile in Patients With Hepatocellular Carcinoma

Abstract: The immune response to TAA were markedly different among the 3 groups, and a correlation with the immune cell profile was observed, suggesting that development of immunotherapy based on the etiology of HCC may lead to more effective treatment outcomes. This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(71 citation statements)
references
References 38 publications
3
65
0
Order By: Relevance
“…33 A second study also showed the presence of a large numbers of both effector Tregs and CTLA-4 þ CD8 þ T cells in nonalcoholic steatohepatitis-related HCC patients, whereas large numbers of PD1 þ CD8 þ T cells were observed in hepatitis B virus-related HCC patients. 34 In a third study, Treg and CD8 þ resident memory T cells were found enriched in a hepatitis B virus-related HCC microenvironment, which also was shown to contain more exhausted T cells than the microenvironment of non-viral-related HCC. 36 Despite these informative studies, a comprehensive assessment of phenotypic and functional T-cell populations in HCC still is lacking.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…33 A second study also showed the presence of a large numbers of both effector Tregs and CTLA-4 þ CD8 þ T cells in nonalcoholic steatohepatitis-related HCC patients, whereas large numbers of PD1 þ CD8 þ T cells were observed in hepatitis B virus-related HCC patients. 34 In a third study, Treg and CD8 þ resident memory T cells were found enriched in a hepatitis B virus-related HCC microenvironment, which also was shown to contain more exhausted T cells than the microenvironment of non-viral-related HCC. 36 Despite these informative studies, a comprehensive assessment of phenotypic and functional T-cell populations in HCC still is lacking.…”
Section: Discussionmentioning
confidence: 94%
“…In recent studies the TIL landscape in HCC has been investigated using different approaches. [33][34][35][36] Single-cell transcriptome studies were performed on small numbers of cells (<150 each in 6 HCC patients) and showed the presence of different CD8 þ populations expanded from a few precursors and characterized by exhausted and regulatory T cell (Treg) signatures. 33 A second study also showed the presence of a large numbers of both effector Tregs and CTLA-4 þ CD8 þ T cells in nonalcoholic steatohepatitis-related HCC patients, whereas large numbers of PD1 þ CD8 þ T cells were observed in hepatitis B virus-related HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…This was a study to comprehensively characterize costimulatory receptor expression on CD8 + TILs and the associated T‐cell activation features in HCC patients. Previous studies describe the expression of 4‐1BB and other costimulatory receptors on CD8 + T cells, but earlier investigations have been limited in that they either used CD8 + T cells from peripheral blood or simply confirmed costimulatory receptor expression on tumor‐infiltrating T cells in HCC . In HCC, 4‐1BB expression was most prominent among the tested activation‐induced costimulatory receptors in CD8 + TILs.…”
Section: Discussionmentioning
confidence: 99%
“…There is growing evidence that inflammation and the immune system are associated with cancer, and the tumor immune microenvironment has proven to be an important driver of biological behavior and a factor affecting chemotherapy (Pico de Coana et al, 2015;Andrejeva and Rathmell, 2017). Also, several studies have found that HCC does not adopt immune privilege, but coordinates powerful immune responses, involving innate and adaptive immune systems, which contribute to the occurrence and development of HCC (Zhou et al, 2017;Inada et al, 2019). The current research indicated the role of 18 immune-associated genes in the regulation of immune pathways and involved in tumorigenesis, which highlighted the value of 18 immuneassociated genes in the study of HCC immune mechanism.…”
Section: Discussionmentioning
confidence: 99%